ANALISIS STRATEGI UNTUK MENINGKATKAN KEUNGGULAN BERSAING - , Civilia Yudhi Aryani ([Yogyakarta] : Universitas Gadjah Mada, 2012)
In the property industry investment value property has been grew to positively. Opening opportunities for many business which is participate on it. PT Citra Kedaton is one of a real estate developer with had survived in Yogyakarta, for ten years implementing corporate strategy to compete with many competitors in the property industry in Yogyakarta. The companies faced particularly difficult the more domestic stiffer rules of the government and limitations of land in Yogyakarta. The position of the company is no longer determining the product, manufacturers are forced to make products according to consumers. Thus, application of appropriate strategies needed to survive and compete to improve the company's competitive advantage in the property industry. On the other hand the whole strategy of activities of the company should be able to improve production efficiency and overcome obstacles. This research will analyzes, the company's strategy that is applied in dealing with the problems already mentioned, also analyzes whether the strategies that applied can increase the competitive advantages for the company. The analysis is done using some theories such as Five Forces (Porter, 1998), SWOT, IE Matrix, SPACE Matrix, Product Market Matrix (Hax and Majluf, 1991), and Value Disciplines (Treacy and Wiersema, 1993), in which all data analysis results will be elabored with these theories.